2017
DOI: 10.1002/polb.24341
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dielectric properties of polymer composite films induced by encapsulated MWCNTs with a one core‐two shell structure

Abstract: Multiwalled carbon nanotubes (MWCNTs) can endow high dielectric constant to polymer-based composites. However, the accompanying poor dispersion of MWCNTs and high dielectric loss for composites severely limit their application in dielectric field. Herein, a modified acid-treated MWCNTs encapsulated by the polyaniline/poly(sodium 4-styrenesulfonate) layers (aMWCNTs@PANI-PSS) with a one core-two shell structure was fabricated by in situ polymerization followed by electrostatic self-assembly technique. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…It is also observed that NDZ105 absorbs at 2917cm -1 and 2850 cm -1 , assigned to asymmetric stretching vibration of methylene and symmetric stretching vibration of methylene, respectively. [24,26] The absorption peaks around 2917cm -1 and 2850 cm -1 in the spectrum of modified TiC, suggest the adherence of NDZ105 to the surface of TiC particles. [20,27] (Scheme 1) ( Fig.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…It is also observed that NDZ105 absorbs at 2917cm -1 and 2850 cm -1 , assigned to asymmetric stretching vibration of methylene and symmetric stretching vibration of methylene, respectively. [24,26] The absorption peaks around 2917cm -1 and 2850 cm -1 in the spectrum of modified TiC, suggest the adherence of NDZ105 to the surface of TiC particles. [20,27] (Scheme 1) ( Fig.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…Huang et al 7 prepared Ag/PVDF nanocomposites by solution blending process. [10][11][12] Among those methods, compounding plays an increasingly significant part owing to its cost-efficiency and high adaptability to actual production. There are also graphene oxide (GO) 8,9 and carbon nanotubes (CNTs).…”
Section: Introductionmentioning
confidence: 99%
“…There are also graphene oxide (GO) 8,9 and carbon nanotubes (CNTs). [10][11][12] Among those methods, compounding plays an increasingly significant part owing to its cost-efficiency and high adaptability to actual production.…”
Section: Introductionmentioning
confidence: 99%